تطور آليات توزيع السكن في التشريع الجزائري مقاربة سوسيو- قانونية - قاسمــي, شوقــي; مرغاد, بشيــر الدين (revue mofakir, 2018)
تسعى هذه المقالة إلى تسليط الضوء على التشريع الناظم لعمليات توزيع السكن الاجتماعي في الجزائر، والوقوف على كل تفاصيله القانونية في قراءة تتبعية تمتد منذ سنة 1962 وإلى غاية يومنا هذا، محاولين من خلالها معرفة أدق تفاصيل التعديلات والتغيرات التي طالته على مدار هذه الفترة، وكذا الظروف والدواعي الاجتماعية المصاحبة لذلك، مضافا إليهما أهم المثالب التي تعتريه اليوم، والتي جعلت عملية منح المساكن خلال السنوات الأخيرة تتحول إلى أحد المشكلات العويصة التي تثقل كاهل السلطات العمومية، جراء كثرة الاحتجاجات التي تتم عقب ذلك وعجزها عن إيجاد حل مناسب لها. Abstract: This article seeks to shed light on the legislation regulating the distribution of social housing in Algeria, and to examine all its legal details in a follow-up reading from 1962 until today, through which we may attempt to find out the most accurate details of the amendments and changes that have occurred over this period and to take a look on the social reasons associated to it. Additionally, it shows to the most important shortcomings raised in the present time which made the process of granting housing, in recent years, turn out to be one of the problems that heavily placed upon the public authorities' shoulders, due to the large number of protests that follow it and the inability to find a suitable solution to it.